Experimental study of vortex-induced vibrations of flexibly mounted cylinder in circulating water tunnel - Shaharuddin, Nik Mohd. Ridzuan (Springer, 2015)
This paper presents the experimental results concerning the vortex-induced vibration phenomena of a flexibly mounted enclosed smooth rigid pipe. The experiment was newly designed and fabricated, utilizing the circulating water tunnel concept. New results on the dynamic response of the vibrating system are shown. The stream flow was generated by using a large displacement volume submersible water tank, controlled through the ABB inverter. The rotation frequency controlled based was implemented in the ABB inverter, and the measurement of stream flow was taken by using a flow rate sensor at the respective pump rotation frequency. The Reynolds number of the experiments ranges from to , and its corresponding reduced velocities, based on the natural frequency in still water, vary up to . The riser modeled pipe was positioned in vertical direction, and it is flexibly mounted at both ends. The system has low mass ratio and damping coefficient, with the values 1.184 and 0.08, respectively. The mass-damping ratio is 0.09472. The results for the bare pipe cylinder in this experimental setup are in good agreementwith othermeasurements found in the literature.